Island Topos in John Fowles' The Magus - Selby, Kamila (Univerzita Pardubice, 2014)
This thesis deals with the portrayal of the island topos in the novel The Magus (1977) by John Fowles. In the initial part of the paper, archetypal patterns of an island topos are captured as well as their essence which resides in human imagination. Special attention is devoted to an island's natural isolation. The insularity is then displayed in two constantly floating antitheses of a paradise and a prison. The core part of this work analyses the island in the aforementioned novel as well as the characters' changing perception of the place. An inseparable part of the analysis includes an interpretation of the island as the Panopticon, Michel Foucault's concept of penitentiary institution.
Topos ostrova v románu Mág Johna Fowlese
Keywords: archetypes; Fowles, John; insularity; island; isolation; Panopticon; prison; Magus; topos; archetypy; Fowles, John; izolace; Mág; ostrov; ostrovnost; Panoptikum; topos; vězení